DIAGNOSIS OF HUMAN SKIN FUNGI USING FORDWARD CHANING METHOD BASED ON - hafzihan ihwana Zihan; Jhonson Efendi Hutagalung jhons; Mardalius Dalius (Jurnal Teknik Informatika (Jutif), 2022)
Expert systems are the process of adopting human knowledge to computers, so that computers can provide solutions like doctors can. The high cost and takes a long time to consult with a skin specialist at the hospital and skin diseases are classified as complaints that can be treated alone. So we need an expert system that makes it easier for experts to diagnose this fungal disease. This research uses qualitative research methods and is included in descriptive research. The method used in this study is the forward chaining method and the search method used is forward data tracing to find conclusions. Data collection techniques through interviews and literature study. This research uses PHP programming language with MySQL database. Based on the results of the comparison between literature studies and interviews, it was found that 4 skin diseases were infected due to fungi so that early symptoms of the disease were diagnosed along with their causes and solutions.